2018
DOI: 10.1177/0885328218815328
|View full text |Cite
|
Sign up to set email alerts
|

A novel curcumin-loaded nanoparticle restricts atherosclerosis development and promotes plaques stability in apolipoprotein E deficient mice

Abstract: Although curcumin possesses anti-atherogenic and anti-inflammatory properties, its application is limited because of its low aqueous solubility and poor oral bioavailability. Recently, our group synthesized a novel linear-dendrimer methoxy-poly (ethylene glycol)-b-poly(ε-caprolactone) copolymer nanoparticle loading curcumin (Cur-NPs) which could improve solubility and release property of curcumin. In the present study, we further evaluated its anti-atherosclerotic effect in apolipoprotein E−/− mice. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Among these, 8 studies [11,[22][23][24][25][26][27] were excluded due to no available outcome data that met our inclusion criteria, and one study [28] was excluded because of the improper participants (not mice). Thus, we included 10 eligible studies [8,9,12,17,18,[29][30][31][32][33] in this systematic review and metaanalysis. Two of the studies [17,18] contained multiple dosages of curcumin and were then considered a total of six independent experiments as we have mentioned in the eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, 8 studies [11,[22][23][24][25][26][27] were excluded due to no available outcome data that met our inclusion criteria, and one study [28] was excluded because of the improper participants (not mice). Thus, we included 10 eligible studies [8,9,12,17,18,[29][30][31][32][33] in this systematic review and metaanalysis. Two of the studies [17,18] contained multiple dosages of curcumin and were then considered a total of six independent experiments as we have mentioned in the eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
“…As described above, plenty of studies reported that different Cur-loaded nanoformulations showed anti-tumor effects for many types of cancer. Furthermore, curcumin nanoformulations exhibited the potential applications for the prevention and treatment of other diseases, such as brain injury, 168,169 wound healing, 170,171 malaria, 172,173 asthma, 174 psoriasis, 175 arteriosclerosis, 176 leishmaniasis, 177 bacterial infection 8 (Table 3), etc.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…The NPs were developed with the aim of passive targeting against atherosclerotic plaque, which demonstrated to selectively reduce the plaque formation in the murine Apo E 2/2 and LDLr 2/2 models, thus confirming the enhancement of redox-based interventions and anti-inflammatory activity in atherosclerosis (Sophie Maiocchi et al, 2020). Dendrimer-based polymer NPs synthesized using methoxy poly (ethylene glycol)-b-poly(ecaprolactone) copolymer encapsulating Curcumin (Cur) is a step in the translation of nutraceutical-based nano delivery approaches which effectively showed a reduction in the atherosclerotic lesion and stabilized the vulnerable plaques in Apo E 2/2 mice (Meng et al, 2019).…”
Section: Polymeric Nps and Lipid Npsmentioning
confidence: 99%